Prevalência da fragilidade no contexto brasileiro e desempenho cognitivo de idosos não frágeis, pré-frágeis e frágeis - Morais Fabrício, Daiene de (Universidade Federal de São Carlos, 2019)
Introduction: The Brazilian population is aging rapidly, which, consequently, leads to an increase in frailty syndrome. Due to the related adverse effects and impacts for the aging individual, the syndrome has been the subject of studies by researchers in the area. Currently, the construct and definition of frailty are still not well established, which leads to discrepancies in the prevalence of frailty around the world and in Brazil. The inclusion of other components, besides the physical, in the conceptual construct of frailty may be one of the aspects that should be considered in this discussion, being the cognitive domain one of the most relevant. Cognitive impairment is one of the main problems affecting the health of the elderly population, and previous studies have evidenced a strong association between frailty and cognition since frail elderly individuals present worse cognitive performance. Thus, two studies were carried out with the following objectives: 1) to review Brazilian studies on the prevalence of frailty syndrome, considering the characteristics of the studied population and the screening methods used; and 2) to investigate differences in cognitive performance general and specific domains among the non-fragile, pre-frail and frail elderly. Method: To achieve the first objective, A systematic review was performed to achieve the first objective. The searches were conducted in the databases PubMed, Scielo, and Web of Science, using the following keywords: (prevalence or epidemiology) and frailty and Brazil. Forty-one articles met the eligibility criteria and were included in the review. In order to reach the second objective, a cross-sectional study was carried out. Two hundred and sixty-seven older adults living in the area covered by a Family Health Center in São Carlos, SP, were evaluated. The elderly were divided into three groups according to the criteria defined by Fried et al. (2001) (non-frail, pre-frail, and frail) using a self-reported instrument for each component of the syndrome. Cognitive performance was assessed with the following instruments: Mini Mental State Examination (MMSE), Consortium to Establish a Registry for Alzheimer's disease (CERAD), Brief Cognitive Screening Battery (BCSB), Similarity Test Cambridge Examination for Mental Disorders (CAMDEX) and digit extension test (direct and inverse order). A multinomial logistic regression analysis adjusted for age, gender and education was performed to evaluate the association between performance in cognitive domains and levels of frailty. Results: In the systematic review, the prevalence of frailty ranged from 3% to 74.1%, depending on the evaluation instrument used, on the region and population studied. Regarding cognitive performance, the frailty was significantly associated with lower scores in the MMSE (RRR = 0.86, p <0.01), memory of the CERAD word list (RRR = 0.92, p = 0.02) and recognition of the list of BCSB figures (RRR = 0.78, p = 0.04). Pre-frailty was associated with lower scores on the memory item of the CERAD word list (RRR = 0.92, p = 0.04) and on the Boston naming test (RRR = 0.82, p = 0.03). Conclusions: The results of these studies showed that the prevalence of the frailty syndrome in Brazil is discrepant. The standardization of screening methods for frailty could facilitate comparisons between studies in order to maximize and create intervention strategies, especially in a country with cultural diversity and regional disparities such as Brazil. Also, the frailty syndrome can impact general cognition and especially memory, learning, and naming. New prospective studies are critical in assessing the relationship between frailty and specific cognitive domains.
Prevalence of frailty in the brazilian context and cognitive performance of non frail, pre-fragil and frail elderly
Keywords: Cognição; Envelhecimento; Fragilidade; Saúde mental; Cognition; Aging; Frailty; Mental health; CIENCIAS HUMANAS::PSICOLOGIA